The Seaward Migration of European Eel at a Continental Scale: A Europe‐Wide Biotelemetry Meta‐Analysis - Pieterjan Verhelst; David Righton; Kim Aarestrup; Pedro R. Almeida; Tea Bašić; Jonathan D. Bolland; Liam Carter; Johan Coeck; José Lino Costa; Justas Dainys; Jan Grimsrud Davidsen; Isabel Domingos; et al. (Fish and Fisheries, 2025)
The European eel ( Anguilla anguilla L.) has a catadromous life cycle, with a single panmictic population that colonises continental Europe and northern Africa yet migrates 5000 to 9000 km to spawn in the Atlantic Ocean. It is unknown how this continental migration is organised so individual eels arrive in time for spawning with conspecifics. This meta‐analysis combined tracking data from 18 water bodies in freshwater and transitional systems distributed along the southwest‐northeast axis of Europe, resulting in a dataset of 2306 eels, making it the most comprehensive in terms of geographical coverage and number of eels tagged. The eels were tracked using acoustic telemetry and the Nedap Trail System and allowed us to study the eel's migration phenology at a continental scale. The findings reveal that the day when eels arrive at sea varies significantly with latitude, with northern eels arriving earlier. Migration speed differs between tidal and non‐tidal habitats, suggesting that tidal currents facilitate faster movement. However, despite these patterns, we observed substantial variability in arrival at sea time and migration speed within water bodies, suggesting that the eel's migration phenology is considerably plastic. The presence of water regulating structures such as weirs, pumping stations and hydropower plants can impact migration timing and speed, potentially delaying eels, but is likely dependent on local hydrological conditions which can be water body specific.

Timing is everything; operational changes at a pumping station with a gravity sluice to provide safe downstream passage for silver European eels and deliver considerable financial savings - Liam J. Carter; Rosalind M. Wright; Robert E. Thomas; Jake Reeds; Leona A. Murphy; Stephen J. Collier; Oliver Evans; Henrik Baktoft; Jonathan D. Bolland (Journal of Environmental Management, 2023)

The impact of extreme flood‐relief pump operations on resident fish in an artificial drain and the potential for artificial habitat introduction - Josh Norman; Jake Reeds; Rosalind M. Wright; Jonathan D. Bolland (Fisheries Management and Ecology, 2023)
Fish are ubiquitous in pumped artificial drains but channel maintenance exposes fish to high flows and predators, and fish communities may experience population‐level threats if they are unable to access refuge during extreme flood‐relief pump operations. We assessed the impact of an extreme flood‐relief pump operation and effects of artificial habitat introduction on a resident fish community in an artificial drain in Great Britain using side‐scan and multi‐beam sonar. Sonar surveys before the flood found abundant aggregations of resident fish, whereas no fish were found after the flood, which suggested flood‐relief pump operations significantly altered resident fish populations. Fish abundance near artificial habitats monitored before the flood were highest during crepuscular periods and was similar among three different artificial habitat designs. Our findings improve the understanding of extreme flood impacts on fish in artificial drains and demonstrate the usefulness of sonar techniques for surveying abundance and spatial distribution of fish populations before and after floods.

Seasonality of biological and physical systems as indicators of climatic variation and change - Jake F. Weltzin; Julio L. Betancourt; Benjamin I. Cook; Theresa M. Crimmins; Carolyn A. F. Enquist; Michael D. Gerst; John E. Gross; Geoffrey M. Henebry; Rebecca A. Hufft; Melissa A. Kenney; John S. Kimball; Bradley C. Reed; et al. (Climatic Change, 2020)

Direct and indirect impacts of pumping station operation on downstream migration of critically endangered European eel - Jonathan D. Bolland; Leona A. Murphy; Robert J. Stanford; Natalie V. Angelopoulos; Nicola J. Baker; Rosalind M. Wright; Jake D. Reeds; Ian G. Cowx (Fisheries Management and Ecology, 2019)
Downstream passage of European eel Anguilla anguilla (L.) in catchments with pump(s) for water level management is a major concern. Catchment‐wide acoustic telemetry revealed silver eels quickly migrated downstream through unobstructed reaches ( n = 12; mean ± SD = 17.9 ± 1.9 km/day). Fourteen of 17 acoustic‐tagged eels detected at the pumping station (82.1%) retreated back upstream and ten (58.8%) passed through pumps after delays (9.5 ± 11.0 days). Multi‐beam sonar imaging across the intake screen (55‐mm gaps) revealed that peaks in migration occurred during the nights preceding the new moon but 76.7% retreated back upstream. All passive integrated transponder ( PIT )‐tagged eels recaptured ( n = 56) downstream of a large (2.23‐m diameter) mixed flow pump survived but 96.5% had minor injuries, reduced physical condition and/or abnormal behaviour. By contrast, 64.7% of PIT ‐tagged eels recaptured ( n = 17) downstream of a small (0.8‐m diameter) axial flow pump died. No acoustic‐tagged eels that passed through the small axial flow pump ( n = 10) performed onward migration at sea, unlike “control” eels released downstream ( n = 11). This evidence may help develop effective remediation measures, such as operational changes, to maximise escapement of catadromous eel species at pumping stations.

Tupinambis merianae as nest predators of crocodilians and turtles in Florida, USA - Frank J. Mazzotti; Michelle McEachern; Mike Rochford; Robert N. Reed; Jennifer Ketterlin Eckles; Joy Vinci; Jake Edwards; Joseph Wasilewski (Biological Invasions, 2015)

A Sex-linked Microsatellite Locus Isolated from the Y Chromosome of Lake Charr, Salvelinus Namaycush - Jake Stein; Kent M. Reed; Chris C. Wilson; Ruth B. Phillips (Environmental Biology of Fishes, 2002)